Role of public education in popularising the field of speech and hearing in India - Mohamed Fazlulla K (Journal of All India Institute of Speech and Hearing, 1970)
Ignorance of the field of speech and hearing in the country has to a greater extent frustrated the young minds of the voung people of the young profession. Ignorance of the utility of the field is also not a healthy sign for its proper growth and development. If the problems of speech and hearing are not identified and treated early due to lack of awareness among the public, rehabilitation becomes rather difficult and may not be effective. ! t frustrates the desire of the professionals who wish to help and also the needs of such children who need professional help. Not many people know about the speech and hearing problems. As a result many cases do not seek the available help. This escalates the intensity of the problem.Thus public education is essential for the total rehabilitation of the community of communicative handicaps. The Alexander Graham Bell Institute in USA as we know it, is solely and mainly concerned with the public education. Likewise the John Tracy Clinic